Intravenous high dose vitamin C and selected antiviral drugs in hospitalized COVID-19 patients: a descriptive cohort study - Mohamad Fleifel; Jonathan Mina; Tony Haykal; Rana Asmar; Ghida El Hout; Ranime Harb; Hani Dimassi; Jacques Mokhbat; Anna Farra; Rola Husni-Samaha (Journal of Infection in Developing Countries)
Introduction: There is lack of universal agreement on the management of COVID-19. Intravenous high dose vitamin C (HDVC), remdesivir (RDV), and favipiravir (FPV) have been suggested as part of the treatment regimens and only RDV is approved by the Food and Drug Administration (FDA) so far. There is no study in Lebanon that addresses the descriptive cohort of HDVC and antiviral therapy amongst COVID-19 inpatients. Our goal was to highlight such a cohort.